A Symmetric Co(N5)2(H2O)4⋅4 H2O High‐Nitrogen Compound Formed by Cobalt(II) Cation Trapping of a Cyclo‐N5− Anion. (22nd March 2017) - Zhang, Chong; Yang, Chen; Hu, Bingcheng; Yu, Chuanming; Zheng, Zhansheng; Sun, Chengguo
Abstract: The reactions of (N5 )6 (H3 O)3 (NH4 )4 Cl with Co(NO3 )2 ⋅6 H2 O at room temperature yielded Co(N5 )2 (H2 O)4 ⋅4 H2 O as an air‐stable orange metal complex. The structure, as determined by single‐crystal X‐ray diffraction, has two planar cyclo‐N5 − rings and four bound water molecules symmetrically positioned around the central metal ion. Thermal analysis demonstrated the explosive properties of the material.